Bank Erosion impact on fishing activities: A case study of Ghurahola village in Majuli District - Acharjya Mohan Das (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
: This study analyzes the impact of bank erosion on fishermen livelihood development. Bank erosion is defined a change in the statistical properties of the landscape in particular region when considered over long periods of time, regardless of cause. However it is classified into two categories namely predictable and unpredictable climate change based on the discussion with village dwellers. In this paper, those bank erosion or degradation of land condition that may occur in coming times could be predicated in advance is defined as predictable climate changes for example precipitation and those climate change or weather condition could not be predictable in advance is defined as unpredictable climate changes for example changing water current. This study focuses on the impact of unpredictable land erosion on the fishermen livelihood development. It has gained a few attentions from the social science researches. The data for this study were collected through informant case studies from fishing village of Ghurahola village located in Majuli District, the largest river island of Assam, India during the intensive fieldwork period of doctoral research, and the qualitative approaches are used for analyzing the data. The finding of this study explores the correlation between the unpredictable landscape change and multi-dimensional paradigm of poverty of the proposed study village as follows: (1) the landscape change of the village from the last two years, (2) the impact of unpredictable changes on fishermen livelihood development activities: occupation uncertainty, income disorganization, damages, loses of fishing equipments and psycho-social problems, and (3) the suggestions and recommendations from this issue. This study analyzed their social problem especially multi-dimensional poverty with the concept of vicious circle which is a key factor for their prolonged poverty and psycho-social problem which is a barrier for livelihood development activities uplifting of this village and suggests that the measures to be taken to reduce the present scenario of the people.